Study of the Influence of Conductive Defect Characteristics on Eddy Current Differential Probe Signal, ISSN 1582-4594 - Benhadda Nabil; Bouchala Tarek; Guettafi Amor; Bachir Abdelhadi (Journal of Electrical Engineering, 2014)
Nowadays, numerical modelling has become an interesting tool for determining impedance variations due to various conductive flaws in eddy current nondestructive evaluation systems. These kinds of defects, rarely treated in the published works, are taken into consideration in the modelling while introducing them as electrically conductive volumes with a finite electric resistivity. This step is very important since it permits to improve qualitatively several models developed so far by many authors whose consider the defect as loss of material only. However, in several applications, the defect can occur with a finite resistivity such as impurity, small burns and micro-solder. On the other hand, even though the defect appears with a loss of materials, som e polluting materials can fill the affected region. Indeed, the volume of the initial defect will be completely or partially occupied by these conducting pollutant materials. This paper deals with the effect of physical and geometrical characteristics of such kind of defects on the differential sensor response. Furthermore, the necessity of taking the defect electric conductivity (as an important parameter) into account will be explained, in order to develop a reliable and accurate inverse method allowing a full characterization of conductive defects.